REVOLUSI RASA TRADISIONAL (INOVASI BAKSO ACI SAMBAL IJO INSTAN OLEH KYLAFOOD) DALAM MENINGKATKAN PENJUALAN - Mahmudi, Mahmudi; lie, Tjhing Man; Taufiq, Achmad (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this research is to analyze the traditional taste revolution (innovation of instant aci sambal ijo meatballs by kylafood) in increasing sales. the type of research is a case study. Data collection techniques are observation, interviews, documentation. Data analysis with miles Huberman. Based on the results of this study, it can be concluded that the innovation of Instant Aci Sambal Ijo Meatballs by Kylafood has succeeded in significantly increasing market acceptance and sales of their products. A well-planned marketing strategy and positive consumer response to the traditional flavors presented are key factors in this success. However, challenges such as wider market penetration and competition with similar products need to be addressed to maintain sustainable growth. Recommendations for Kylafood include further development of innovative product variations as well as strengthening more aggressive marketing strategies to maintain their position in this competitive market